The Effect of Adding Cr and RE on the CO2 Corrosion Resistance of Carbon Steel - WANG Guofu, ZHANG Yuling, DENG Xuyan, ZHANG Lingtong, TIAN Qingchao (Cailiao Baohu)
In order to study the effect of adding Cr and rare earth (RE) on the CO2 corrosion resistance of carbon steel， 25Mn2， 1Cr and 1CrRE steels were used to simulate the corrosion behavior under the downhole corrosion environment in autoclave.The corrosion films on the three kinds of steels were analyzed by optical microscope， scanning electron microscope， energy spectrometer and X-ray diffractometer.Results showed that adding 1Cr to carbon steel could reduce the corrosion rate by 23%， and adding RE to 1Cr steel could increase the corrosion resistance of CO2 by 40%.It was found that the corrosion film was mainly composed of FeCO3 and a small amount of FeOOH， as well as dotted Fe3C in the inner layer.Additionally， the corrosion films of 25Mn2 and 1Cr steel had a two-layer structure， but the corrosion films of 1CrRE steel had a three-layer structure with the Cr element enrichment at the interface.Research suggested that the carbon pickup phenomenon observed in the corrosion film was caused by the reaction between Fe3 C and carbonic acid.Furthermore， rare earths reduced the spacing between FeCO3 crystal planes， which facilitated the denser growth of FeCO3 crystals and hindered ion transport.On the one hand， they were beneficial for CO2 corrosion resistance，and on the other hand，they also made the corrosion film of 1CrRE steel appear in a three-layer structure.